2014
DOI: 10.5539/ass.v10n9p262
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Usage of Language Learning Strategies and the Level of Proficiency in Learning Arabic Ab Initio

Abstract: This study was aimed to investigate the relationship between Language Learning Strategies (LLS) and the level of proficiency of students in Arabic Ab Initio language. There were also several studies done to investigate the achievement of students and their frequent usage of these Language Learning Strategies. Meanwhile, the level of student proficiency was measured by their results based on college-level exam results before they were registered in the Arabic Ab Initio classes. 162 year 1 students were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Previous studies also found that more successful ESL/EFL learners tend to make more frequent use of learning strategies overall (e.g., Ghani, Mahfuz, Saad, & Yusoff, 2014;Akbari, 2003, Green & Oxford, 1995Murray, 2010;Wharton, 2000). Some studies also examined the learners' cultural backgrounds.…”
Section: Learning Strategy and Language Proficiencymentioning
confidence: 99%
“…Previous studies also found that more successful ESL/EFL learners tend to make more frequent use of learning strategies overall (e.g., Ghani, Mahfuz, Saad, & Yusoff, 2014;Akbari, 2003, Green & Oxford, 1995Murray, 2010;Wharton, 2000). Some studies also examined the learners' cultural backgrounds.…”
Section: Learning Strategy and Language Proficiencymentioning
confidence: 99%
“…The learning process is closely related to learning media (Wekke & Lubis, 2016). The appropriate media chosen by the teachers will make the learning process easier, fun, not boring, and not stagnant (Ghani et al, 2014). Media includes a physical tool to convey teaching material or content such as books, films, videos, slides, and others (Albantani & Madkur, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is also referred to as a tool to achieve goals of education (Moh. Ulum, Siti Maisuroh, Rafika Milania, 2021), all activities have been neatly and systematically arranged (Ghani, Mahfuz, & Saad, 2014). Therefore, it can be said that the success or failure of a teaching and learning process in an educational institution cannot be separated from the curriculum (Albantani & Madkur, 2017).…”
Section: Introductionmentioning
confidence: 99%